Risk of intussusception after monovalent rotavirus vaccine (Rotavac) in Indian infants: A self-controlled case series analysis. Issue 1 (3rd January 2021) - ,; Das, Manoja Kumar; Arora, Narendra Kumar; Poluru, Ramesh; Tate, Jacqueline E.; Gupta, Bini; Sharan, Apoorva; Aggarwal, Mahesh K.; Haldar, Pradeep; Parashar, Umesh D; Zuber, Patrick L.F.; Bonhoeffer, Jan; et al.
Abstract: Background: An association between rotavirus vaccination and intussusception has been documented in post-licensure studies in some countries. We evaluated the risk of intussusception associated with monovalent rotavirus vaccine (Rotavac) administered at 6, 10 and 14 weeks of age in India. Methods: Active prospective surveillance for intussusception was conducted at 22 hospitals across 16 states from April 2016 through September 2017. Data on demography, clinical features and vaccination were documented. Age-adjusted relative incidence for 1–7, 8–21, and 1–21 days after rotavirus vaccination in children aged 28–364 days at intussusception onset was estimated using the self-controlled case-series (SCCS) method. Only Brighton Collaboration level 1 cases were included. Results: Out of 670 children aged 2–23 months with intussusception, 311 (46.4%) children were aged 28–364 days with confirmed vaccination status. Out of these, 52 intussusception cases with confirmed receipt of RVV were included in the SCCS analysis. No intussusception case was observed within 21 days of dose 1. Only one case occurred during 8–21 days after the dose 2. Post-dose 3, two cases in 1–7 days and 7 cases during 8–21 days period were observed. There was no increased risk of intussusception during 1–7 days after the doses 1 and 2 (zero cases observed) or dose 3 (relative incidence [RI], 1.71 [95% confidence interval CI 0.0–5.11]). Similarly, no increased risk during 8–21 days after the dose 1 (zero cases observed), dose 2 (RI, 0.71 [95% CI, 0.0–3.28]) or dose 3 (RI, 2.52 [95% CI, 0.78–5.61]). The results were similar for 1–21 day periods after the doses separately or pooled. Conclusions: The risk of intussusception during the first 21 days after any dose of rotavirus vaccine (Rotavac) was not higher among the Indian infants than the background risk, based on limited SCCS analysis of 52 children.